2020
DOI: 10.2147/ott.s246278
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Long Noncoding RNA ZFAS1 Potentiates the Development of Hepatocellular Carcinoma via the microRNA-624/MDK/ERK/JNK/P38 Signaling Pathway</p>

Abstract: Background: A long noncoding RNA (lncRNA), ZNFX1 antisense RNA 1 (ZFAS1), was increased in multiple cancers, including hepatocellular carcinoma (HCC), resulting in malignancy development and progression. However, the mechanisms involving the interaction between ZFAS1 and microRNA-624 (miRNA-624) remain largely unknown. Therefore, the goal of this study was to probe the functional role of ZFAS1 in the development of HCC and its underlying mechanism. Methods: Firstly, differentially expressed lncRNAs in HCC tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Non‐coding RNAs, including micro‐RNAs (miRNAs) and long non‐coding RNAs (lncRNAs), have been established as potential tumor suppressors or oncogenes and play key regulators in tumor development. lncRNA ZNFX1 antisense RNA 1 (ZFAS1) has been shown to be involved in HCC progress, and its upregulation correlates with poor prognosis and promotes malignant phenotype 30,31 . It has been speculated that there is a relation between ZFAS1, miR‐624 (a tumor suppressor micro‐RNA), and MDK in HCC.…”
Section: Mdk and Hepatocellular Carcinomamentioning
confidence: 99%
“…Non‐coding RNAs, including micro‐RNAs (miRNAs) and long non‐coding RNAs (lncRNAs), have been established as potential tumor suppressors or oncogenes and play key regulators in tumor development. lncRNA ZNFX1 antisense RNA 1 (ZFAS1) has been shown to be involved in HCC progress, and its upregulation correlates with poor prognosis and promotes malignant phenotype 30,31 . It has been speculated that there is a relation between ZFAS1, miR‐624 (a tumor suppressor micro‐RNA), and MDK in HCC.…”
Section: Mdk and Hepatocellular Carcinomamentioning
confidence: 99%
“…And the carcinogenic molecular mechanism of ZFAS1 has been partly clari ed that it usually functions as CeRNA of miRNA to regulate downstream mRNA expression to affect manifold biological behaviors of tumor cell. Duan et al found that ZFAS1 was obviously overexpressed in HCC and connected with worse prognosis of HCC patients, and silencing of ZFAS1 can suppress cell proliferation, invasion, migration and epithelial-mesenchymal transition (EMT) through regulation of the miR-624/MDK/ERK/JNK/AKT signaling pathway [11]. Several researchers have demonstrated that ZFAS1 was upregulated in CRC and can serve as a prognostic factor for CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The included 2263 patients all come from China. 16 types of tumors were included in this study, which contains pancreatic adenocarcinoma (PAAD) [10], hepatocellular carcinoma (HCC) [11,18], melanoma [12], esophageal squamous cell carcinoma (ESCC) [13,19], hepatoblastoma (HB) [20], cholangiocarcinoma (CCA) [14], papillary thyroid carcinoma (PTC) [21], prostate cancer (PCa) [22], clear cell renal cell carcinoma (ccRCC) [15], colorectal cancer (CRC) [16,23,24], bladder cancer [25,26], nasopharyngeal carcinoma (NPC) [27], gastric cancer (GC) [28], epithelial ovarian cancer (EOC) [29], non-small cell lung cancer (NSCLC) [30], glioma [31]. ZFAS1 expression in tumor tissues were all detected by qRT-PCR.…”
Section: Details Of Included Studymentioning
confidence: 99%
“…MDK plays an important role in resistance of CTCs to anoikis through activation of PI3K/Akt/NF-kB/TrkB signaling. MDK can be involved in HCC progression and metastasis via ERK/JNK/p38MAPK-mediated signaling promoted by long lncRNA ZFAS1 [ 145 ]. The ZFAS1 expression is elevated in HCC but can be suppressed by miR-624.…”
Section: Promising Proteomic Biomarkers Of Hccmentioning
confidence: 99%